2010
DOI: 10.1523/jneurosci.5719-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Localization of Muscarinic M1Receptor on Dendritic Shaft and Spine of Cortical Pyramidal Cells and Its Anatomical Evidence for Volume Transmission

Abstract: Acetylcholine (ACh) plays important roles for higher brain functions, including arousal, attention, and cognition. These effects are mediated largely by muscarinic acetylcholine receptors (mAChRs). However, it remains inconclusive whether the mode of ACh-mAChR signaling is synaptic, so-called "wired," transmission mediated by ACh released into the synaptic cleft, or nonsynaptic, so-called "volume," transmission by ambient ACh. To address this issue, we examined cellular and subcellular distribution of M 1 , th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
184
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(197 citation statements)
references
References 62 publications
11
184
1
1
Order By: Relevance
“…This finding is supported by electron microscopy studies showing that ␣4* nAChRs are detected near the plasma membrane of neuronal cell bodies and apical dendritic shafts, but not typically at postsynaptic densities (Nakayama et al, 1995;Commons, 2008). Whether ␣4* nAChR are directly apposed by cholinergic terminals is not entirely clear, however our immunofluorescence data suggest a loose spatial relationship between ␣4* nAChRs and cholinergic terminals, similar to that described for ␣7 nAChRs and muscarinic receptors (Jones and Wonnacott, 2004;Yamasaki et al, 2010).…”
Section: Subcellular Distribution Of ␣4* Nachrs In Somatosensory Cortexsupporting
confidence: 84%
“…This finding is supported by electron microscopy studies showing that ␣4* nAChRs are detected near the plasma membrane of neuronal cell bodies and apical dendritic shafts, but not typically at postsynaptic densities (Nakayama et al, 1995;Commons, 2008). Whether ␣4* nAChR are directly apposed by cholinergic terminals is not entirely clear, however our immunofluorescence data suggest a loose spatial relationship between ␣4* nAChRs and cholinergic terminals, similar to that described for ␣7 nAChRs and muscarinic receptors (Jones and Wonnacott, 2004;Yamasaki et al, 2010).…”
Section: Subcellular Distribution Of ␣4* Nachrs In Somatosensory Cortexsupporting
confidence: 84%
“…Mouse cDNA fragments of the CCK1 receptor (nucleotides 348-1658bp; GenBank accession number, NM_009827), pepsinogen C (1-1352bp; NM_025973.3), and c-Kit (37-1320bp; BC052457.1) were subcloned into the pBluescript II plasmid vector. Digoxigenin (DIG)-or fluorescein-labeled cRNA probes were transcribed in vitro for FISH analysis (Yamasaki et al 2010). The fragmentation of riboprobes by alkaline digestion was omitted in order to increase the sensitivity and specificity.…”
Section: Fluorescent In Situ Hybridization (Fish) Techniquementioning
confidence: 99%
“…Yamasaki et al examined cellular and subcellular distribution of M 1 receptors in the cerebral cortex and hippocampus, and demonstrated that M 1 receptors are expressed preferentially in glutamatergic pyramidal neurons, and scarce or undetectable in various GABAergic interneuron subtypes (Yamasaki et al, 2010). Instead of M 1 receptors, M 3 receptors were detectable in interneurons (Yamasaki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of M 1 receptors, M 3 receptors were detectable in interneurons (Yamasaki et al, 2010). Using mice genetically lacking specific muscarinic receptor subtypes, receptor subtypes responsible for cholinergic modulation of ion channels have been identified in hippocampal pyramidal neurons (Dasari and Gulledge, 2011;Rouse et al, 2000).…”
Section: Discussionmentioning
confidence: 99%